Fiestas Patrias Mexican Independence 1995 - Reception Grand Marshal, Charles Esparza (and Other Event) - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of an American GI Forum reception, with Charles Esparza, Grand Marshal of the 1995 Fiestas Patrias Mexican Independence Parade, as the guest of honor (17:20). Also included is a live music performance (00:00).